The use of faculty policy teams for advancing policy advocacy and colleagueship. Issue 4 (1st June 2020) - Smith, Yvonne M.; Cleveland, Kimberly A.; Fisher, Jason; Kleman, Carolyn
Abstract: Policy changes that impact nursing occur at multiple levels. The scope and pace of policy changes make it impossible for one faculty member to fill the role of policy advocate. Faculty are frequently reticent to participate, yet, policy work can be very rewarding for faculty. When engaged in policy advocacy, nursing faculty can be a valuable resource to the university, to legislators, and to other stakeholders. This article discusses the team approach to policy advocacy activity and outlines key steps in the policy process. Strategies for overcoming barriers when merging academic and advocacy responsibilities are identified. An example of a college of nursing faculty policy team that utilized nursing presence and their combined intellectual, social, and political capital is provided. In this example, the policy team influences policy discussions on issues impacting both the university community and citizens throughout the state. The strategies provided and the policy process steps discussed are applicable to policy changes at the local, state, and federal levels. Nursing faculty are positioned to engage students, alumni, practice leaders, and community stakeholders in interdisciplinary and transdisciplinary efforts that influence policy initiatives.